Environmentally Oriented Anti-Crisis Management of Enterprises: Problems, Directions, and Prospects - BALTABAYEVA, Ainur; BEKMETOVA, Aruna; KYLYSHPAYEVA, Bibigul; ASSANOVA, Zhanna; ZHUNUSSOVA, Gulshat (Journal of Environmental Management and Tourism, 2020)
The article deals with the issues of environmentally oriented anti-crisis management of enterprises. The authors consider environmentally oriented logistics approaches, analyze the ecological and economic status of the Republic of Kazakhstan, and study the experience of developed countries, such as the United States, Germany, Canada, Ireland, China, and Korea, in managing the green economy. Based on international experience in environmentally oriented economic management, promising tools for managing the transition to a green economy have been developed. According to the authors of the article, the main tools of environmentally oriented anti-crisis management of enterprises are the following: conducting a mandatory environmental audit to determine unbiased findings on the environmental impact; creating regional environmental funds for financial support of environmental activities of enterprises; and trading quotas for limited environmental impact. The theoretical and practical significance of the work lies in the possibility of using the main provisions and conclusions in the development of a contemporary market concept of anti-crisis management of the green economy of both an individual enterprise and the country in general.